ANALYSIS OF WORKING CAPITAL TURNOVER ON PROFIT MARGIN IMPROVEMENT IN PT. JATI JAYA PERKASA MANDIRI IN MAKASSAR - Sunarti, Sunarti; Muttalib, Abdul; Daweng, H.A Muhiddin (Jurnal Ekonomi Balance, 2018)
This study has the purpose to know The Work Capital Turnover in terms of increasing profit margin in PT Jati Jaya Perkasa Mandiri period 2014-2017. The subjects in this study were PT. Jati Jaya Perkasa Mandiri and research objects Financial statements for the period 2014-2017 covering items in the Balance Sheet and Income Statement report. Data collection method used in this research is documentation. Data analysis method used in this research was financial ratio analysis. Based on the results of research, it can be known that the performance of working capital management is seen from (1) the turnover of working capital is categorized as  less because under 6 times (2) the increase of profit margin at company PT. Jati Jaya Perkasa Mandiri in 2014 amounted to 11.18% means that each rupiah sales generate profits of Rp 0.1118. Consecutive profit margin in 2015 amounted to 11.84% or increased by 0.66% compared to 2014; in 2016 of 8.30% or decreased by 3.54% compared to 2015; year 2017 of 7.91% or decreased by 0.39% compared to 2016.